Navalnyy v. Russia (Eur. Ct. H.R.). (25th April 2019) - Heri, Corina
Abstract : On November 15, 2018, the European Court of Human Rights (ECtHR) issued its judgment in Navalnyy v. Russia . The applicant in the case argued that the Russian authorities had targeted him for arrest and administrative sanctions because of his political activism. In its judgment, the Grand Chamber confirmed its recent change in approach to Article 18 of the European Convention on Human Rights (ECHR), including the normalization of the provision's scope and burden of proof. However, it displayed continued uncertainty about how to deal with measures based on a mixture of legitimate and illegitimate purposes.